2011
DOI: 10.1353/hpu.2011.0168
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Acidosis and pH Regulation in Central Respiratory Chemoreceptors

Abstract: Dysfunctions of brainstem regions responsible for central CO2 chemoreception have been proposed as an underlying pathophysiology of Sudden Infant Death Syndrome (SIDS). We recorded respiratory motor output and intracellular pH (pHi) from chemosensitive neurons in an in vitro tadpole brainstem during normocapnia and hypercapnia. Flash photolysis of the H+ donor nitrobenzaldehyde was used to induce focal decreases in pHi alone. Hypercapnia and flash photolysis significantly decreased pHi from normocapnia. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This adverse effect has been demonstrated in other preparations [1]. Therefore other methods of focal intracellular acidification which do not disrupt central respiratory rhythmicity and chemoreception, such as uncaging H + with ultraviolet light [38], should prove beneficial in further describing the correlation between respiratory motor output and pHi.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This adverse effect has been demonstrated in other preparations [1]. Therefore other methods of focal intracellular acidification which do not disrupt central respiratory rhythmicity and chemoreception, such as uncaging H + with ultraviolet light [38], should prove beneficial in further describing the correlation between respiratory motor output and pHi.…”
Section: Discussionmentioning
confidence: 93%
“…Studies in other animal preparations using pH-sensitive probes have also identified differences in the pHi regulatory processes of cells located in chemosensitiveand non-chemosensitive regions [34][35]. In addition, using BCECF in tadpole brainstem neurons to record pHi optically does not disrupt respiratory rhythmicity or central respiratory chemoreception [36][37][38]. The pHi regulatory responses to hypercapnic acidosis reported in this study are consistent with those reported in the snail [39] and rat [6,34,35], indicating the evolutionary conservation of pHi regulatory mechanisms, although the persistence of pHi regulation in non-chemosensory cells, as seen in all tadpole developmental stages, is observed only in preparations from neonatal mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular acidosis is a major inhibitor of IKr (27), and occurs in a variety of pathological situations associated with cardiac dysfunction, including SIDS and myocardial ischemia (28-30). Consequently, a large body of work has explored the impact of extracellular protons on hERG1 (27,31-37).…”
Section: Introductionmentioning
confidence: 99%